PEMIKIRAN DAN PRAKTEK PEMERINTAHAN ADAT SUKU DAYAK MA’ANYAN DI KALIMANTAN TENGAH - Kisno Hadi (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
This article describes the thought and practice of the Adat government of the Dayak Maanyan tribe in Central Kalimantan. In Adat's thought, the government is forming and setting Adat laws. Adat itself is not only a set of legal forms of laws but includes all aspects of the daily life of the tribe. Using the descriptive-explanatory method, this article will describe, identified and explore the forms of the thought and facts of the Adat Government that gathered in Hukum Adat, Taliwakas (stories of leadership), and Tingkah (wisdom advice of tribal chief/Adat leader). Research results found that  Adat is the source of authority to govern a tribal society. It is contain a leadership concept, ethnic state, agreement, the hierarchy of the community and government system. This aspect is a basis of the recognition that Adat Government “Government that rule by the law”. But, in the colonial era and in the Indonesian government, Adat separated from the formal government itself: Adat becomes an-sight “Adat laws”. Nowadays, Adat only has authority in Adat institution, not part of government anymore.